2014
DOI: 10.1007/s00167-014-2907-7
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative hyperglycaemia and incidence of post-operative complications in patients undergoing total knee arthroplasty

Abstract: Retrospective case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 31 publications
1
29
1
Order By: Relevance
“…A previous study found an association between HbA 1c levels C 8 and wound complications but no association with early postoperative deep infection in patients with DM after TKA [6]. On the other hand, our finding of the only association of preoperative FBG C 200 mg/dL with superficial surgical site infection is in contrast with previous studies reporting the association of preoperative FBG level C 126 mg/dL [9], postoperative FBG level C 126 mg/dL [21], and postoperative FBG level C 200 mg/dL [16] with the occurrence of complications after total joint arthroplasty. Our findings, taken together with previous studies, suggest that surgeons should think carefully before performing this elective procedure in a patient with HbA 1C C 8 or FBG C 200 mg.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…A previous study found an association between HbA 1c levels C 8 and wound complications but no association with early postoperative deep infection in patients with DM after TKA [6]. On the other hand, our finding of the only association of preoperative FBG C 200 mg/dL with superficial surgical site infection is in contrast with previous studies reporting the association of preoperative FBG level C 126 mg/dL [9], postoperative FBG level C 126 mg/dL [21], and postoperative FBG level C 200 mg/dL [16] with the occurrence of complications after total joint arthroplasty. Our findings, taken together with previous studies, suggest that surgeons should think carefully before performing this elective procedure in a patient with HbA 1C C 8 or FBG C 200 mg.…”
Section: Discussioncontrasting
confidence: 99%
“…Prior studies have suggested that patients with DM undergoing TKA have a higher likelihood of wound complications and surgical site infections than those without DM [5,6,8,18,20,21,28]. Hence, achieving optimal glycemic control in patients with DM is important.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SIH is a form of hyperglycemia seen secondary to stress. Trauma of any kind causes a bodily response characterized by enhanced metabolism and hyperglycemia [1,2].…”
Section: Introductionmentioning
confidence: 99%